IFN-α kinoid in systemic lupus erythematosus: results from a phase IIb, randomised, placebo-controlled study. Issue 3 (23rd December 2019) - Houssiau, Frederic A; Thanou, Aikaterini; Mazur, Minodora; Ramiterre, Edgar; Gomez Mora, Danny Alexis; Misterska-Skora, Maria; Perich-Campos, Risto Alfredo; Smakotina, Svetlana A; Cerpa Cruz, Sergio; Louzir, Bassem; Croughs, Thérèse; Tee, Michael Lucas
Abstract : Objective: To evaluate the efficacy and safety of the immunotherapeutic vaccine interferon-α kinoid (IFN-K) in a 36-week (W) phase IIb, randomised, double-blind, placebo (PBO)-controlled trial in adults with active systemic lupus erythematosus (SLE) despite standard of care. Methods: Patients with SLE (185) with moderate to severe disease activity and positive interferon (IFN) gene signature were randomised to receive IFN-K or PBO intramuscular injections (days 0, 7 and 28 and W12 and W24). Coprimary endpoints at W36 were neutralisation of IFN gene signature and the BILAG-Based Composite Lupus Assessment (BICLA) modified by mandatory corticosteroid (CS) tapering. Results: IFN-K induced neutralising anti-IFN-α2b serum antibodies in 91% of treated patients and reduced the IFN gene signature (p<0.0001). Modified BICLA responses at W36 did not statistically differ between IFN-K (41%) and PBO (34%). Trends on Systemic Lupus Erythematosus Responder Index-4, including steroid tapering at W36, favoured the IFN-K and became significant (p<0.05) in analyses restricted to patients who developed neutralising anti-IFN-α2b antibodies. Attainment of lupus low disease activity state (LLDAS) at W36 discriminated the two groups in favour of IFN-K (53% vs 30%, p=0.0022). A significant CS sparing effect of IFN-K was observed from W28 onwards, with a 24% prednisone daily dose reduction at W36 in IFN-K compared with PBO (p=0.0097). The safety profile of IFN-K was acceptable. Conclusions: IFN-K induced neutralising anti-IFN-α2b antibodies and significantly reduced the IFN gene signature with an acceptable safety profile. Although the clinical coprimary endpoint was not met, relevant secondary endpoints were achieved in the IFN-K group, including attainment of LLDAS and steroid tapering. Trial registration number: NCT02665364 .